Digital Entrepreneurial Orientation, Social Media Capability, and SME Performance: Evidence from Indonesian Local Economies - Ce Gunawan; Galih Raspati; M. Afrizal Maulana (Universitas Airlangga, 2026)
Background: Digital transformation has reshaped the business landscape, making digitalization a key driver of competitiveness. This shift is important for Micro, Small, and Medium Enterprises (MSMEs), given their strategic role within Indonesia's economic. Although MSMEs contribute substantially to national GDP and employment, many remain unable to leverage digital technologies to drive performance improvements fully. Prior empirical investigations have produced mixed findings regarding the influence of Digital Entrepreneurial Orientation (DEO) on firm performance, suggesting that factors such as Social Media Capability (SMC) may play a mediating role in explaining these inconsistencies. Objective: This study examines (1) how Digital Entrepreneurial Orientation (DEO) affects SME performance; (2) DEO's impact on Social Media Capability (SMC); (3) the effect of SMC on SME performance; and (4) how SMC mediates the DEO-SME performance relationship. Method: This study used SEM-PLS to analyze survey data from 100 West Java MSME owners or managers involved in digital operations. This research examined relationships among digital entrepreneurial orientation (a firm’s approach to digital opportunities), social media capability (the use of social media tools), and organizational performance. Results: The analysis demonstrates that DEO exerts both direct and indirect effects on SME performance, with SMC functioning as a significant conduit between the two. Specifically, firms that cultivate stronger social media capabilities are better positioned to translate their digital entrepreneurial orientation into tangible gains in innovation output, customer engagement quality, and operational efficiency. Conclusion: The results confirm that both DEO and SMC contribute meaningfully to MSME performance outcomes, validating the complementarity between the Resource-Based View and Dynamic Capability Theory. From a pragmatic point of view, the study indicates that it is important to introduce digital capacity-building programmes to encourage innovation, risk-taking, and proactive digital behaviour in the evolving digital economy, thereby improving MSMEs' competitiveness. Keywords: Digital Entrepreneurial Orientation; Dynamic Capability; Indonesia; SME Performance; Social Media Capability